Documents relating to the constitutional history of Canada, 1759-1791 - Doughty, Arthur G. (Arthur George), Sir, 1860-1936; Shortt, Adam, 1859-1931 (Sessional paper (Canada. Parliament) ;, 1907)
"The present volume is the first of a short series ... [and] contains only documents relating to the central portion of Canada known at the time as the Province of Quebec, between the period of the Cessation and the passing of the Constitutional Act in 1791."--Intro.